Cultural revolution and political ambivalence in Zhao Xiaosheng’s Two Ballades for piano solo - Ke, Xue; Loo, Fung Ying; Loo, Fung Chiat; Xiaohang, Wang (University of Ljubljana, 2021)
The ascendancy of China’s Cultural Revolution led to a purge of the rightists, including musicians. This article unveils composer Zhao Xiaosheng’s emotional entanglement of fear and suppressed hostility toward the revolution, reflected in the political and artistic ambivalence in his two ballades for solo piano composed after his father’s death.